PRELIMINARY CARE: THE IMPORTANCE OF DERMAL MANAGEMENT - Ranieri, Regina; Simão, Daniele; Ribeiro Marques, Brenda; Teodora Ribeiro, Eunice; Teruo Suguihara, Roberto (Health and Society, 2023)
The concern with self-care has been growing, often among women, but the search for improved self-esteem also inflames men. Today there is a catalog of procedures, surgical and non-surgical, with variables of cost- effectiveness, technique and accessibility. Statistics show that from 2014 to 2016 there was a 390% increase in the demand for non-surgical aesthetic procedures in Brazil. The skin preparation is an essential step to ensure the quality of the result of the procedure performed. Before starting to apply any product, it is important to prepare the skin so that it is clean, hydrated, and protected. This includes removing impurities, toning, moisturizing, and applying sunscreen. Proper skin preparation helps improve product adhesion, prevents infection at the surgical site, and ensures that the skin looks healthy and radiant. The knowledge gained in this study is the facial cleansing system essential for cell regeneration, facial rejuvenation, oil control, skin whitening, clove and blackhead removal, improved uniformity, significant pigmentation and improved It was concluded that it showed significant benefits of local oxygenation, more youthfulness. It improves the finish of cosmetics used after cleansing and increases ease of removal. Based on free radicals, it delays premature aging of the skin and contributes to skin health and beauty. In summary, the goal is to present how skin preparation is a fundamental step in managing the procedure to be performed, taking care of the skin before, during and after, through the literature review.